Practices of Reproduction Regulation as a Reflexion of Gender Ideologies. The Case of Spain and Serbia in the 20th Century (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The objective of this paper is to present a comparative analysis of reproductive ideologies in Spain and Serbia, as these are considered important for the construction of gender ideologies. It is also part of the hypothesis that these two countries could be paradigmatic models for socio-cultural system of patriarchy over several centuries, but with two very different social and political developments in the second half of the 20th century and the early 21st century, which, however, have created a very similar social reality. The examined historical moment (from early 20th century until the second half of the same century) covers a period of great turmoil not only in Serbia and Spain, but globally. Reproductive policies are chosen as the object of analysis because they are considered an important element of gender ideologies and, therefore, potentially decisive for the emancipation of women.
Keywords: gender ideologies; reproductive politics; patriarchy; Serbia; Spain